1992
DOI: 10.1037/0033-2909.112.2.330
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory role of serotonin in neural information processing: Implications for human psychopathology.

Abstract: Investigation of the role of 5-hydroxytryptophan (5-HT), which functions as a modulator in the central nervous system, across behavioral contexts suggests that a general principle of transmitter function may be derived that is independent of specific behaviors and specific neural loci. A functional principle of 5-HT action in neural information processing in the central nervous system is proposed. Extremes deviations in 5-HT activity result in biases in information processing that may have direct effects on be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
284
1
9

Year Published

1995
1995
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(309 citation statements)
references
References 207 publications
(391 reference statements)
15
284
1
9
Order By: Relevance
“…Furthermore, although they did not differ from participants in the other two groups on CANTAB measures of cognitive performance or on self-report measures of anxiety and mood at the time of testing, at least 25% of the total sample of 41 ecstasy-using participants, reported that they believed that taking ecstasy had made them more susceptible to anxiety, depression, aggression/irritability, and mood swings, and also reduced their ability to concentrate. If high error rates on the MFF20 reflect reduced ability to cope with high levels of cognitive demand, and ecstasy causes reductions in brain serotonergic activity, the present results are also consistent with the view that 5-HT plays an orchestrating role in cognition, and that extreme deviations of 5-HT activity can result in biases in cognitive processing, which can predispose individuals to pathological conditions such as impulsive behavior, violent suicide, and aggression (Spoont 1992). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, although they did not differ from participants in the other two groups on CANTAB measures of cognitive performance or on self-report measures of anxiety and mood at the time of testing, at least 25% of the total sample of 41 ecstasy-using participants, reported that they believed that taking ecstasy had made them more susceptible to anxiety, depression, aggression/irritability, and mood swings, and also reduced their ability to concentrate. If high error rates on the MFF20 reflect reduced ability to cope with high levels of cognitive demand, and ecstasy causes reductions in brain serotonergic activity, the present results are also consistent with the view that 5-HT plays an orchestrating role in cognition, and that extreme deviations of 5-HT activity can result in biases in cognitive processing, which can predispose individuals to pathological conditions such as impulsive behavior, violent suicide, and aggression (Spoont 1992). …”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, there is evidence that disorders of central serotonergic neurotransmission, as reflected by low levels of 5-HIAA, are associated with anxiety (e.g., Garvey et al 1995), impulsive and aggressive personality traits (e.g., Linnoila et al 1993), and suicidal behavior (Traskman-Bendz et al 1986). It has also been proposed that 5-HT may play an orchestrating role in cognition, and that extreme deviations of 5-HT activity can result in biases in cognitive processing (Spoont 1992) and impairments in learning and memory (e.g., Hunter 1988). Despite this evidence, the possible long-term psychological sequelae of ecstasy use in humans has received relatively little attention from researchers, partly because most controlled laboratory studies of the effects of repeated administration of ecstasy are precluded for legal and ethical reasons.…”
mentioning
confidence: 99%
“…For us, constraint lacks ties to a specific motivational system, which is supported by the traits that cluster around the constraint dimension in Figure 3. We suggest that constraint functions as a threshold variable that modulates stimulus elicitation of motor behavior, both positive and negative affects, and cognition, all of which may be associated with serotonin functioning (Depue 1995;Depue & Spoont 1986;Depue & Zald 1993) as was also proposed by others (Panksepp 1982;Soubrie 1986;Spoont 1992; Zuckerman 1991b Figure 3. A plotting of loadings of personality traits derived from 11 studies in which more than one multidimensional personality questionnaire was jointly factor analyzed as a means of deriving general traits of personality.…”
supporting
confidence: 55%
“…The foUlJwing stimulation parameters were used: 20 mA, 2 ms, 3 Hz for 2 min. The fIlSt stimulation period (S 1) was alwavs used as control and 2-methyl-5-HT (10,30,100 1lM) was added 8 min before Sz and remained present unlil the end of the experiment. Nisoxeline.aselective noradrenaIine reuptake inhibitor (FuIler et al.…”
Section: Treatmentsmentioning
confidence: 99%